Kepemimpinan Kepala Sekolah Dalam Implementasi Manajemen Berbasis Sekolah Di Sd Negeri 1 Boyolali Tahun Ajar 2016/ 2017 - Aulia, Annisa Risqi, Minsih, S.Ag, M.Pd (2017)
Principal Leadership in School Based Management (Leadership Studies at SD Negeri 1 Boyolali). This study aims to determine the implementation of the leadership of SD Negeri 1 Boyolali principal in the implementation of School Based Management. One key to success lies in the role and function of the principal in implementing the MBS model. Good leadership is certainly very impact on the achievement of organizational goals because the leader has an influence on the performance he leads. The ability to know a group to achieve its goals is part of leadership. So the principal has a strategic role to achieve that goal. The principal must prepare to be able to implement it as expected to achieve the desired goal. Implementation of principal leadership tasks revealed in the task of assessment, empowerment, involvement, motivation and participation of administrative staff, teachers, students, parents and the community in connection with the implementation of School Based Management in SD Negeri 1 Boyolali. As a leader, manager, educator, motivator, administrator, supervisor, and innovator, the principal successfully implemented SBM in SD Negeri 1 Boyolali.